Sectoral human capital spillovers: Evidence from Turkey - (:unkn) unknown (BILGESEL YAYINCILIK SAN & TIC LTD, 2011)
Evidence based on the data from the 2004-2008 Household Labor Surveys, demonstrates the existence of within sector knowledge spillovers in Turkey Estimates from a two step regressions confirm prior findings for different countries. Job tenure proxying for on the job training is a source of human capital externality We further discuss various labor market characteristics pertaining to this result. We show that the externality effects of education and job tenure reinforce each other once a threshold is crossed. Our results confirm the findings of recent literature emphasizing social interactions between workers as major sources of spillover For bigger firms, the estimated externality effect is stronger
Keywords: human capital; externalities; returns to education; growth; EDUCATION; GROWTH